New type of transverse moving box mechanism for pot seedling transplanting machine - Zhou, Maile; Hua, Zhengyu; Wang, Jingyuan; Wang, Lei; Zhao, Yun; Yin, Daqing (International Journal of Agricultural and Biological Engineering, 2018)
The existing moving box mechanism pot seedling transplanting machine on the market moves too fast when the picked seedling is collected, which negatively impacts the seedling picking performance. In order to improve the performance, two types of variable speed continuous moving box schemes were designed in this study. The first scheme was to apply a spiral-gear moving box spiral shaft with sine curve characteristics in the box moving mechanism, whereas the second one was to change the circular gear in the moving box into an elliptical gear with a speed shifting transmission mechanism. The working mechanism of the mechanical structure was analyzed, and the kinematic model was established. A dynamic analysis of the slider mechanism was performed. A virtual prototype was established according to agronomic parameters, and the virtual prototype experiments were conducted in ADAMS. The physical prototype and the high-speed photography experiment were performed on the test bench of a transplanting machine frame. The theoretical analysis, virtual prototype and physical prototype test results were consistent, which verified the validity of the theoretical model, virtual prototype and physical prototype and ensured the feasibility of the system. Keywords: transplanting machine, rice transplanter, pot seedling, moving box mechanism, variable speed moving box, spiral shaft, elliptic gear DOI: 10.25165/j.ijabe.20181102.2867 Citation: Zhou M L, Hua Z Y, Wang J Y, Wang L, Zhao Y, Yin D Q. New type of transverse moving box mechanism for pot seedling transplanting machine. Int J Agric & Biol Eng, 2018; 11(2): 70–75.